EFFECTS OF TETRAALKYLAMMONIUM SALTS ON ALKALINE HYDROLYSIS OF N-(2-METHOXYPHENYL) PHTHALIMIDE - Yoke Leng, Sim; Khan, M. Niyaz; Ariffin, Azhar (Malaysian Journal of Science, 2004)
The effects of the concentrations of Meâ‚„NCI, Prâ‚„NCl, Buâ‚„NCl, Meâ‚„NBr, Prâ‚„NBr and Buâ‚„NBr on the rate of alkaline hydrolysis of N-(2-methoxyphenyl)phthalimide (N-2MPhPT) at 35Â°C and in Hâ‚‚0 solvent containing 2 % (v/v) CHâ‚ƒCN reveal the formation of ion-pair complexes between solvent - separated loose ion-pair forms (M^n^+ â‹¯ X^k^-) and N-2MPhPT. The bulky hydrophobic tails of tetraalkylammonium salts and their halide anions inhibit the reaction by blocking the OHâ» nucleophilic attack on the reactive site of N-2MPhPT. Among all the quaternary ammonium salts, Meâ‚„NCI showed slight inhibition only because of the shielding effect created by the methyl group is very small. However, Buâ‚„NBr presents the greatest inhibition on hydrolysis rate because of its strong binding affmity with N-2MPhPT.The effects of the concentrations of Meâ‚„NCI, Prâ‚„NCl, Buâ‚„NCl, Meâ‚„NBr, Prâ‚„NBr and Buâ‚„NBr on the rate of alkaline hydrolysis of N-(2-methoxyphenyl)phthalimide (N-2MPhPT) at 35Â°C and in Hâ‚‚0 solvent containing 2 % (v/v) CHâ‚ƒCN reveal the formation of ion-pair complexes between solvent - separated loose ion-pair forms (M^n^+ â‹¯ X^k^-) and N-2MPhPT. The bulky hydrophobic tails of tetraalkylammonium salts and their halide anions inhibit the reaction by blocking the OHâ» nucleophilic attack on the reactive site of N-2MPhPT. Among all the quaternary ammonium salts, Meâ‚„NCI showed slight inhibition only because of the shielding effect created by the methyl group is very small. However, Buâ‚„NBr presents the greatest inhibition on hydrolysis rate because of its strong binding affmity with N-2MPhPT.